Multidecadal Wind Variability Drives Temperature Shifts on the Agulhas Bank. Issue 5 (8th May 2019) - Malan, Neil; Durgadoo, Jonathan V.; Biastoch, Arne; Reason, Chris; Hermes, Juliet
Abstract: The Agulhas Bank is an important area for the spawning of small pelagic fish and other species. Here, within a NEMO ocean model, we investigate changes in temperature over the Bank on multidecadal time scales. In agreement with previous observational studies, a shift to colder temperatures is found in 1997. The model also simulates an earlier shift from colder to warmer temperatures in 1966. These shifts are coastally confined and shown, using a climatologically forced model run as a control, to be driven by a north‐south migration in the large‐scale wind belts, rather than by changes in downward heat fluxes or changes in the Agulhas Current itself. The zonal wind changes on the Agulhas Bank show a significant relationship with the Southern Annular Mode, showing some promise for future predictability of cold and warm regimes on the Agulhas Bank. Thus, while the Agulhas Current has been shown in previous work to have a large impact on intra‐annual and interannual temperature variability, this work shows that multidecadal variability in temperature on the shelf is likely to be wind forced. Key Points: A regional ocean model is used to examine multidecadal shelf temperature changes on the Agulhas Bank There are distinct shelf temperature regime changes in 1966 and 1996 These regime shifts are caused by changes in coastal upwelling linked to large‐scale wind variability